Impact of One-Week Administration of Dihydrotestosterone in Rat Anterior Pituitary Gland. (21st October 2022) - Kanasaki, Haruhiko; Tumurbaatar, Tuvshintugs; Cairang, Zhouma; Tumurgan, Zolzaya; Oride, Aki; Okada, Hiroe; Kyo, Satoru
Abstract : Hyperandrogenism causes dysfunction of the hypothalamic–pituitary–gonadal (HPG) axis in reproductive women. In this study, we examined the effects of dihydrotestosterone (DHT) on characteristic changes in rat anterior pituitary gland samples. DHT was administered to ovary-intact 6-week postnatal female rats for 7 days, after which the anterior pituitary glands were examined and compared with those in control rats. Estrous cyclicity was not drastically disrupted by DHT treatment. Common gonadotropin α subunit ( Cga ), luteinizing hormone β subunit ( Lhb ), and follicle-stimulating hormone (FSH) β subunit ( Fshb ) gene expression levels were not modulated by DHT treatment, while prolactin ( Prl ) gene expression was significantly repressed by DHT. Gonadotropin-releasing hormone (GnRH) receptor ( Gnrh-r ) gene expression was significantly inhibited by DHT, whereas pituitary adenylate cyclase-activating polypeptide (PACAP) receptor ( Pca1-r ) gene expression was increased by DHT. Gene expression levels of the receptors encoded by thyrotropin-releasing hormone ( Trh-r ) and kisspeptin ( Kiss1-r ) genes were unchanged. Expression of inhibin α subunit ( Inha ) and activin β A subunits ( Actba ) within the pituitary was inhibited by DHT treatment, while activin B subunit ( Actbb ) and follistatin ( Fst ) gene expression was unchanged by DHT. In mouse pituitary gonadotroph L β T2 cells, DHT did not modulate the gene expression of Gnrh-r, but it inhibited the expression of Inha and Actba subunits within the L β T2 cells. In rat prolactin-producing GH3 cells, DHT did not modulate prolactin gene expression, but it increased Pac1-r gene expression. The present observations suggest that DHT directly or indirectly affects the anterior pituitary gland and induces characteristic changes in hormone-producing cells.